2022
DOI: 10.1097/mao.0000000000003594
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hypofractionated Stereotactic Radiosurgery in Facial Nerve Schwannoma

Abstract: ObjectiveIn the current era of modern neurosurgery, the treatment strategies have been shifted to “nerve-preservation approaches” for achieving a higher facial and hearing function preservation rate following facial nerve tumors. We have conducted this novel report on determining the outcome of patients with facial nerve schwannomas (FNS) treated with hypofractionated stereotactic radiosurgery (hfSRS).PatientsRetrospective chart review of a prospectively maintained database search was conducted.InterventionPat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A previous study reported that the treatment-induced exacerbation of facial nerve paralysis significantly increased with surgery, whereas there was no significant difference in local control rates between surgery and radiotherapy for intracranial facial nerve schwannomas [15]. Regarding local tumor control rate, preservation of facial nerves, and hearing ability, hypofractionated stereotactic radiosurgery is reported to be more beneficial in radiosurgery [16 ▪▪ ].…”
Section: Facial Nerve Schwannomamentioning
confidence: 95%
“…A previous study reported that the treatment-induced exacerbation of facial nerve paralysis significantly increased with surgery, whereas there was no significant difference in local control rates between surgery and radiotherapy for intracranial facial nerve schwannomas [15]. Regarding local tumor control rate, preservation of facial nerves, and hearing ability, hypofractionated stereotactic radiosurgery is reported to be more beneficial in radiosurgery [16 ▪▪ ].…”
Section: Facial Nerve Schwannomamentioning
confidence: 95%